Suicide rate in the dental profession: Fact or myth and coping strategies - Brian M Lange; Eric Y. K. Fung; David G Dunning (Wolters Kluwer Medknow Publications, 2012)
This article summarizes relevant scientific data on the alleged high suicide rate among dentists as compared to other health care professions. Potential contributing risk factors for the dental profession are identified. In addition, a brief review is provided for major depressive disorder, a contributor to increased suicide, along with its symptoms, underlying theory, drug treatment and coping skills to combat this disorder.